Formulation of Palmarosa (Cymbopogon Martinii) Essential Oil Emulgel Using Sodium Carboxymethyl Cellulose (Na-CMC) as A Gelling Agent - Odilia Putri Daniati; Disa Andriani; Muhammad Saiful Amin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Palmarosa essential oil (Cymbopogon martinii) is known for its potential as a natural therapeutic agent. It contains geraniol compounds with demonstrated antimicrobial and anti-inflammatory activity. However, direct application of palmarosa essential oil to the skin is less effective and may cause irritation. Objective: This study aimed to develop a topical formulation in the form of an emulgel containing palmarosa essential oil, using sodium carboxymethyl cellulose (Na-CMC) as the gelling agent. Method: The emulgel was prepared in three different formulations containing 2%, 4%, and 6% concentrations of palmarosa essential oil. The resulting preparations were evaluated for quality through organoleptic properties, homogeneity, pH, spreadability, adhesion, and emulsion type. Data were statistically analyzed using one-way ANOVA. Results: The emulsion type test indicated that all formulations were oil-in-water (o/w) emulsions. Differences in palmarosa essential oil concentration influenced the physical properties of the emulgel, but all three formulations met the standard requirements for good physical quality of emulgel preparations.Conclusions: the three emulgel formulations containing palmarosa essential oil fulfilled the standards for acceptable physical properties.